Description of the imago of Meridialaris spina Pescador & Peters 1987 (Insecta: Ephemeroptera) - Pessacq, Pablo (Zootaxa, 2010)
The genus Meridialaris Peter & Edmunds, 1972 (Ephemeroptera: Leptophlebiidae) was established to include all South American Deleatidium Eaton, 1884 (Peter & Edmunds 1972). The only exception was D. vittatum Thew, 1960, a species described from Brazil and latter synonymized with Ulmeritoides haarupi (Esben-Petersen, 1912) by Peters et al. (2005). As the type species of the genus, Peters and Edmunds (1972) designated M. laminata (Ulmer, 1920). Pescador & Peters (1987) described three new species and synonymized other two.